2022
DOI: 10.1002/pip.3618
|View full text |Cite
|
Sign up to set email alerts
|

Mass production of crystalline silicon solar cells with polysilicon‐based passivating contacts: An industrial perspective

Abstract: Silicon solar cells that employ passivating contacts featuring a heavily doped polysilicon layer on a thin silicon oxide (TOPCon) have been demonstrated to facilitate remarkably high cell efficiencies, amongst the highest achieved to date using a single junction on a silicon substrate. Importantly, it has been shown that the polysiliconbased passivating contacts have a high degree of compatibility with existing mass production processes and toolsets, making them an attractive choice for photovoltaic (PV) cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The removal of the poly-Si from the front side and of the edges is thus of utmost importance [1,5]. There are ideas to avoid the wrap-around completely by using physical vapor deposition (PVD) [6] or PECVD masks [7] and this would naturally reduce the required amount of TOPCon process steps [8]. The parasitical poly-Si can successfully be removed by e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of the poly-Si from the front side and of the edges is thus of utmost importance [1,5]. There are ideas to avoid the wrap-around completely by using physical vapor deposition (PVD) [6] or PECVD masks [7] and this would naturally reduce the required amount of TOPCon process steps [8]. The parasitical poly-Si can successfully be removed by e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] The process of TOPCon technology is highly compatible with existing production lines and thus it is considered to be the next‐generation technology after PERC. [ 6 ] TOPCon solar cells have attracted attention in the PV community and gained a substantial market share after Feldmann et al reported an efficiency of more than 23%. [ 7 ] TOPCon solar cells incorporate at the rear side passivating contacts consisting of n‐type polycrystalline silicon (poly‐Si) and interfacial SiO x layers.…”
Section: Introductionmentioning
confidence: 99%
“…[25,41] The development of poly-Si or other layers alloyed with oxygen or carbon is crucial in the TOPCon concept to enable carrier selectivity. [6,25,35,38,[42][43][44][45][46] There are multiple techniques that can be used to deposit this layer. PECVD, [23,25,35] low-pressure chemical vapor deposition (LPCVD), [28] as well as sputtering [47] are used to deposit amorphous/polycrystalline silicon thin films.…”
Section: Introductionmentioning
confidence: 99%